Implementasi Akad Murabahah Dalam Perbankan Syariah di Indonesia - Riyadi, Farrel Maulana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Murabahah contract is one of the most widely used financing schemes in Islamic banking. This study aims to analyze the implementation of the Murabahah contract in Islamic banking in Indonesia, including regulatory aspects, practical applications, and the challenges faced. Using the normative legal research method, this study examines relevant laws, fatwas, and case studies from several Islamic banks in Indonesia. The findings indicate that Murabahah is implemented based on DSN-MUI fatwas and OJK regulations but faces challenges related to compliance, risk management, and competitive pricing. Furthermore, this study highlights how Murabahah plays a crucial role in financing sectors such as property, vehicles, and business investments, making it a key driver of Islamic banking growth. However, issues such as information asymmetry, public awareness, and price competition with conventional banking remain challenges that need to be addressed. This study concludes that although Murabahah is the dominant contract, improvements in regulation, financial literacy, and risk management strategies are necessary to enhance its effectiveness and sustainability in the Islamic banking industry in Indonesia.